ANALISIS STANDAR AKUNTANSI PEMERINTAHAN DALAM MEWUJUDKAN TRANSPARANSI DAN AKUNTABILITAS KEUANGAN (Studi : Kantor Kecamatan Siantar Kabupaten Simalungun) - Jessica Caroline Purba (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to analyze the management of financial reports at the Siantar District Office using Government Accounting Standards (SAP) as the main reference framework in realizing Financial Transparency and Accountability. The research method used is a qualitative descriptive study with an observational analysis approach, financial report documentation and interviews with relevant parties in Siantar District. The results of the study indicate that the implementation of SAP has been effective as a guideline in the preparation of transparent, accountable, orderly, and accurate financial reports, with complete and systematic financial documents. However, there are limitations in terms of information disclosure to the public caused by technological constraints, internal policies, and human resource capacity, so that transparency to the public is not optimal. Financial accountability in Siantar District is implemented with strict procedures and regular supervision through audits by the inspectorate and the Supreme Audit Agency (BPK). Although there has been positive progress, improvements in literacy, transparency, and information disclosure mechanisms are needed to make supervision more participatory and credible. Overall, financial management in Siantar District demonstrates a strong commitment to transparent, accountable, and trustworthy financial governance to improve the quality of public services.